Identification and Prioritization of Challenges and Development Technologies in One of Iran's Oil Fields in a Well-based Approach - Yasin Khalili; Mohammadreza Akbari; Hossein Heirani; Mohammad Ahmadi (Journal of Chemical and Petroleum Engineering)
The development and production of oil and gas reservoirs in Iran, possessing one of the largest oil reserves globally, face significant challenges. To address these challenges effectively, this paper employs modern techniques, including the Technology Tree and Morin Model, to identify and prioritize the challenges and solutions for the technological advancement of an Iranian oil field. Through collaboration with experts, target technology areas and oil field challenges are identified, and their priority is determined using the Morin Model. Key technologies in these areas are identified through questionnaires and expert consultations. Challenges such as advanced drilling techniques, enhanced oil recovery methods, and efficient reservoir management are highlighted, with prioritization crucial for resource allocation. The study focuses on south Iran, primarily examining the period from the late 1960s to the present day, with a particular emphasis on reservoir and well behavior, especially within the Ilam formation. A multidisciplinary expert committee, including representatives from the National Iranian Oil Company, Amirkabir University of Technology, and Iran Offshore Oil Company, oversaw the research. The validation of results was conducted through questionnaires and interviews, resulting in the development of a roadmap for oil field technologies in collaboration with relevant experts. Key technological solutions include improving drilling methods, utilizing downhole sensors, hydraulic fracturing, acidizing, and deploying smart systems in producing wells. This comprehensive framework emphasizes collaboration, validation, and prioritization in addressing technological challenges in Iran's oil industry, ensuring practical and effective solutions.